Dampak Pariwisata terhadap Pembangunan Ekonomi di Solo Valley Desa Prangi Kecamatan Padangan Kabupaten Bojonegoro - Moch Fachrul Ibad; Gesa Bimantara (Pusat Riset dan Inovasi Nasional, 2025)
The development of Solo Valley tourism in Prangi Village, Padangan District, Bojonegoro Regency, has made a significant contribution to the improvement of the local economy, social, and environment. Through the 2025 Bojonegoro University Group 19 KKN program, a series of activities will be carried out such as tourism business management training, digital marketing assistance, the formation of youth business groups, and collaboration with BUMDes. One of the strategic steps taken is the socialization of the Geopark concept, which not only highlights the geology, history, and cultural potential of the Solo Valley, but also prioritizes educational and conservation aspects in tourism development. Data from the results of the activity showed an increase in the number of tourism business actors by up to 200%, an increase in the average income of residents by 50%, and community participation in tourism management reached 82%. In addition, there is an improvement in environmental quality, especially through an increase in the water quality index. Geopark socialization also encourages the diversification of tourism products, opens up new job opportunities, and increases public awareness of the preservation of natural resources and local culture. The success of this program is inseparable from the active involvement of the community, academic assistance, and village institutional support. Efforts to integrate community empowerment, digital technology, and the Geopark concept open up new innovation spaces in managing tourism based on local potential. The challenges faced, such as limited infrastructure, human resource capacity, and financing sustainability, require further attention so that the benefits obtained can continue to develop optimally.